State and dynamic output feedback control of switched linear systems via a mixed time and state-dependent switching law. (November 2016) - Zhai, Ding; Lu, An-Yang; Li, Jing-Hao; Zhang, Qing-Ling
Abstract: This paper investigates the problem of robust control for switched linear systems with dwell-time constraint. First, a mixed time-dependent and state-dependent switching law is proposed. The stability analysis and weighted L 2 gain analysis are proposed based on the Lyapunov–Metzler inequality method and average dwell-time technique. Then by using discretized Lyapunov function technique, the state feedback controllers and dynamic output feedback controllers are designed to stabilize the switched linear systems and satisfy a weighted L 2 gain performance under the proposed dwell-time switching law. The method proposed in this paper can reduce the numbers of the switches. Finally the effectiveness of proposed method is illustrated through three simulation examples.